Host and viral factors that determine the clinical outcome of hepatitis C virus genotype 3a infection - Humphreys, I; Isla S. Humphreys (2011)
HCV infects 170 million persons worldwide and is a serious global health problem. Genotype-3a is the dominant genotype in newly diagnosed infections within the UK and has a high response rate to interferon therapy, with up to 70% patients achieving a sustained virological response (SVR). The reason(s) for this are unknown; therefore the aim was to assess host and viral factors that determine treatment outcome of subtype-3a infection. Full-length subtype-3a viral sequence analysis identified 2 novel regions of hypervariability within E2 - HVR495 and HVR575, that are subject to positive selection pressure. A 5 amino-acid insertion found only in subtype-3a and a putative glycosylation site were contained within HVR575. These data suggest that HVR495 and HVR575 may serve as major antigenic sites in subtype-3a HCV infection. Successful treatment of chronic subtype-3a infection was not associated with pre-treatment quasispecies diversity and complexity, PePHD, HVR495 or HVR575 sequence. Different patterns of quasispecies variation were observed in patients that failed treatment. Subtype-3a specific CD8+ T-cell responses in chronic infection target non-structural proteins, in contrast to pre-dominant genotype-1 core-specific CD4+ T-cell responses. SVR was associated with a decline in subtype-3a specific and non-specific T-cell responses, and also total lymphocyte counts, which all recovered after treatment. These data do not support the theory that clearance of subtype-3a is associated with an enhancement of antiviral T-cell responses. Overlapping peptides detected a greater number of subtype-3a T-cell responses compared with peptides representing putative predicted CD8 epitopes. Therefore subtype-3a HCV is distinct from genotype-1 in terms of genome sequence, effect of treatment on quasispecies and subtype-3a specific T-cell responses, further emphasising the importance in understanding this distinct subtype.